Relevance of Nutrient-Limited Phytoplankton Production and Its Bacterial Remineralization for Carbon and Oxygen Fluxes in the Baltic Sea - Piontek, Judith; Endres, Sonja; Le Moigne, Frédéric A. C.; Schartau, Markus; Engel, Anja (Frontiers in Marine Science, 2019)
The Baltic Sea is prone to oxygen deficiency due to the restricted water exchange with the North Sea in coincidence with a high biological oxygen demand. The partitioning of organic carbon between respiration, accumulation and export is co-determined by phytoplankton primary production and its subsequent bacterial remineralization. Here, we investigated net phytoplankton primary production, heterotrophic bacterial biomass production and dark CO2 fixation by on-board incubations with radiolabeled tracers in the Baltic Proper and in the Gulf of Riga after the main spring bloom. Results show that low phytoplankton standing stocks of ≤1.6 µg chlorphyll a L-1 sustained net primary production of 161-724 mg C m-2 d-1 under nitrogen limitation. Estimates of bacterial carbon remineralization suggest that freshly produced organic carbon was supplied to the aphotic zone at all stations. In the southern Baltic Proper, net primary production exceeded the bacterial carbon demand in the upper mixed layer, suggesting that organic matter derived from nutrient-limited primary production was available for export to bacterial communities below the oxycline. On average, 46% of heterotrophic bacterial production was mediated in oxygen minimum zones, revealing the high importance of organic matter recycling under hypoxic and anoxic conditions for the carbon budget. Dark CO2 fixation of up to 4.33 µg C L-1 d-1 in sulfide-free waters equaled 9-54% of the co-inciding heterotrophic bacterial carbon demand and may have provided another organic carbon source for heterotrophic activity. Substantially higher dark CO2 fixation up to 25.46 µg C L-1 d-1 was determined in sulfidic waters. Since our study was conducted five months after the major Baltic inflow event in winter 2014/2015, potential effects of deep water ventilation could be investigated. In the Gotland Basin, heterotrophic bacterial production in renewed oxygen-rich bottom water was similar to that in the uplifted oxygen-deficient former bottom water, while it was significantly reduced in sulfidic waters. Hence, our results suggest that the removal of hydrogen sufide by inflow events has a high potential to increase bacterial carbon remineralization.